Do erro sobre os elementos em branco das leis penais: uma análise a partir do direito penal socioeconômico brasileiro - Frederico Gomes de Almeida Horta (2013)
This paper is a dogmatic analysis of the legal-criminal theories and corresponding legislative solutions about the consequences of error by the author of an objectively typical conduct on the criminally relevant characteristics or the misdemeanor of his conduct when the fact is punishable according to a blank criminal law. It intends to contribute to clarify the nature and legal consequences of the error on the blank elements in criminal law, especially when the ignorance or mistake of the agent affects the extra-criminal duty imposed by the supplemental norm. It begins with a conceptual outline of the blank elements in criminal law, in relation to normative elements of the type and the elements of global valuing of the fact. There is an overview of the evolution of the legal treatment of the error and the systematic organization of this content by criminal scholarship, transversely guided to the solutions provided from the main versions of the theory of intention, and the theory of culpability toward the error that falls upon the normative elements of criminal law, and especially upon the blank elements. The material reasons that determine the blank criminal laws are examined, identifying the functions they have in socio-economic criminal law. From the very theory of culpability, in a limited version, it is concluded that the extra-criminal duty imposed by the norms of supplementation of blank criminal laws compose the type, as its imperative element, whenever indispensible to confer the objective sense of the offense to a legal asset. Finally, the existence of an imperative element is identified in the unfair types of abstract danger configured by mere conduct and defined by blank criminal laws, in this way demonstrating the suitability of the limited theory of culpability, through its material foundations, also for the treatment of error in socio-economic criminal law.